If it is a duck, it should quack :three descriptive elements that influence television advertisement success from the perspective of teenagers in Kuching, Sarawak - Goh, Poi Chiaw (Universiti Malaysia Sarawak, 2005)
The main aim of this study is to determine whether there are significant relationships between the three descriptive elements (involvement, message, and celebrity) and the TV advertisement effectiveness based on the purchase intention